Narwhal hunting by Pond Inlet Inuit: An analysis of foraging mode in the floe-edge environment - Lee, David; Wenzel, George (Études/Inuit/Studies, 2004)
AbstractThe harvesting of narwhals by Baffin Island Inuit represents an important relationship in terms of the continuous utilization of an indigenous marine resource. However, research on Inuit hunting with respect to narwhals has been mainly confined to harvest counts despite the major role narwhals play in the local northern Baffin subsistence system. The present research examines Pond Inlet Inuit foraging behaviour for narwhals in the spring floe-edge environment. While sea ice is one of the most dominant features of the arctic marine environment for much of any year, it is in the spring that the dynamism of its physical and biological characteristics is most notable. This was especially evident at the fast ice-open water interface, or floe-edge, where rapid physical change in the condition of the ice is frequent and summer migratory marine mammals and birds are present in large numbers. In this paper, analysis of 14 observed hunts indicates that Inuit utilization of the spring floe edge for narwhal hunting, in contrast to most other hunt types, follows a sit-and-wait mode of foraging. The study also explicates aspects of Pond Inlet hunters traditional ecological knowledge necessary to travel and conduct harvesting operations successfully in this complex environment.